(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Observation on the seasonal variations of hydrological condition and turgidity of selected Robusta coffee clones has been carried out in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute in Jember. The aim was to evaluate the effect of hydrological variation on the coffee plants and the degree of soil moisture effect on plant performance. Experimental site overlays on alluvial plain, + 45 m a.s.l., 8o 15’ South with D rainfall type. Observation was conducted by survey method at the experimental plots of organic fertilizer and nitogen treatments on selected Robusta coffee clones derived from rooted cuttings, i.e. BP 436, BP 42, BP 936 and BP 358. Observation was only conducted at the experimental blocks of organic matter trials of 20 l/tree/year at nitrogen (Urea) application of locally recommanded rate during the subsequent years of 1999 to 2001. Parameters observed included plant turgidity and soil moisture content of three different depths, i.e. 0—20, 20—40 and 40—60 cm and the weather. Observation was carried out in five replicates designed as blocks of barn manure treatment and N-fertilizer of recommended rate as basal fertilizer. The results showed that meteorological condition and soil moisture of experimental site through the years have seasonal patterns following the seasonal pattern of rainfall. Compared to other meteorological characteristics, relative humidity dominantly determined evaporation and plant turgidity. Plant turgi-dity was not only determined by soil moisture condition, but also atmospheric demand. When relative humidity (RH) was relatively high, plant turgidity was relatively stable although soil moisture of surface layers was very low, and the reversal when soil moisture content was high plant turgidity was controlled by atmospheric demand (relative humidity). With a 3—4 dry month period, relative turgidity of the coffee plants was relatively stable above 82%, except when soil moisture of 60 cm surface layer was below 25% (w/w) and or atmospheric demand was relatively high (RH 85%). Soil moisture contents of deeper soil layers seemed to have greater impact on the plant turgidity and the deeper the soil layers the narrower the seasonal variation of their soil moisture contents. Selected different clones originated from rooted cuttings showed different response to water stress and could be put in order from the most sensitive to water stress as follows BP 436, BP 42, BP 936 and BP 358. Barn manure application could significantly increase soil moisture content but its influence could not significantly increase plant turgidity. Key words : Seasonal variation, atmospheric condition, soil moisture, plant turgidity, Robusta coffee clones.